Material modelling and parameter identification for sheet-bulk metal forming - Schmaltz, Stefan; Willner, Kai (Proceedings of the XII International Conference on Computational plasticity - Fundamentals and Applications, 2013)
In this paper an anisotropic material model at finite strain is implemented and utilised in a commercial Finite Element Software via a User-Subroutine. The material model is based on an additive split of the logarithmic strains to model the anisotropic finite strain behaviour of the material. The material parameters of the non-linear hardening and the orthotropic anisotropy are identified through an inverse Finite Element Model Updating procedure and verified with experimental testing. The chosen material is a sheet steel, which has a low initial yield strength and a high hardening capacity and therewith is typically used in deep-drawing and sheet-bulk metal forming processes.
UnivIS-Import:2015-04-16:Pub.2013.tech.FT.FT-TM.materi_6
Keywords: Anisotropy; Computational plasticity; FEMU; Parameter identification; Sheet-bulk metal forming